Benzene induces haematotoxicity by promoting deacetylation and autophagy. Issue 2 (8th November 2018) - Qian, Shanhu; Han, Yixiang; Shi, Yifen; Xu, Wanling; Zhu, Yiyi; Jiang, Songfu; Chen, Yi; Yu, Zhijie; Zhang, Si; Yang, Yiping; Yu, Kang; Zhang, Shenghui
Abstract: Chronic exposure to benzene is known to be associated with haematotoxicity and the development of aplastic anaemia and leukaemia. However, the mechanism underlying benzene‐induced haematotoxicity, especially at low concentrations of chronic benzene exposure has not been well‐elucidated. Here, we found that increased autophagy and decreased acetylation occurred in bone marrow mononuclear cells (BMMNCs) isolated from patients with chronic benzene exposure. We further showed in vitro that benzene metabolite, hydroquinone (HQ) could directly induce autophagy without apoptosis in BMMNCs and CD34 + cells. This was mediated by reduction in acetylation of autophagy components through inhibiting the activity of acetyltransferase, p300. Furthermore, elevation of p300 expression by Momordica Antiviral Protein 30 Kd (MAP30) or chloroquine reduced HQ‐induced autophagy. We further demonstrated that in vivo, MAP30 and chloroquine reversed benzene‐induced autophagy and haematotoxicity in a mouse model. Taken together, these findings highlight increased autophagy as a novel mechanism for benzene‐induced haematotoxicity and provide potential strategies to reverse this process for therapeutic benefits.